Issuer Compliance with Disclosure Principles in Insider Trading in the Indonesian Capital Market: A Comparative Study with Singapore and the United States from an Investor Protection Perspective: Kepatuhan Emiten Terhadap Prinsip Disclosure dalam Insider Trading di Pasar Modal Indonesia Perbandingan dengan Singapura dan Amerika Serikat: Perspektif Perlindungan Investor - Joeliant, Hanz Bryan; Gunadi, Ariawan (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Insider trading and weak information disclosure undermine market integrity and investor protection. Specific Background: In Indonesia, disclosure obligations under the Capital Market Law, OJK regulations, and IDX rules remain limited in timeliness, insider categorization, and enforcement compared to Singapore and the United States. Knowledge Gap: Existing studies have not systematically compared issuer compliance with disclosure principles across these jurisdictions to assess their effectiveness in preventing insider trading. Aims: This study analyzes Indonesia’s disclosure framework, compares it with Singapore and the U.S., and evaluates necessary reforms to enhance investor protection. Results: Findings show Indonesia’s two-day disclosure window, narrow insider definition, and predominantly administrative sanctions weaken deterrence, while Singapore’s immediate disclosure model and the U.S.’s broad misappropriation theory, real-time surveillance, and strong enforcement provide higher compliance and detection levels. Novelty: This research integrates doctrinal, conceptual, and comparative analyses to demonstrate how adopting broader insider definitions, accelerated disclosure, and technology-driven monitoring can strengthen Indonesia’s regulatory structure. Implications: Strengthening OJK–IDX integration, enhancing surveillance capacity, reforming insider trading provisions, and adopting international best practices are essential to improving market transparency and long-term investor confidence. Highlights: Indonesia’s disclosure rules remain slower and less comprehensive than Singapore and the U.S. Broader insider definitions and real-time surveillance improve detection and deterrence. Strengthened OJK–IDX integration is essential for effective enforcement and investor protection. Keywords: Insider Trading, Disclosure, Investor Protection, Capital Market Regulation, Comparative Study